2009
DOI: 10.1016/j.pec.2009.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Health care provider attitudes toward patients with acute vaso-occlusive crisis due to sickle cell disease: Development of a scale

Abstract: Objective Patients with sickle cell disease (SCD) often perceive negative provider attitudes, which may affect the quality of patient–provider communication and care during vaso-occlusive crises (VOCs). This study investigated the validity and reliability of a scale to measure provider attitudes toward patients with acute VOC. Methods Using a cohort of adults with VOC (September 2006 to June 2007), we administered a 10-item provider questionnaire within 72 h of patient encounters. After factor analysis, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 42 publications
1
47
1
Order By: Relevance
“…2,14 The construct validity of our outcomes was assessed using the previously validated Medical Condition Regard Scale (MCRS), which measures the extent to which respondents find patients with a given medical condition to be enjoyable, treatable, and worthy of medical resources. 15 Clinicians expressing more negative attitudes about SCD patients were hypothesized to exhibit lower regard for these patients as measured by the MCRS.…”
Section: Methodsmentioning
confidence: 99%
“…2,14 The construct validity of our outcomes was assessed using the previously validated Medical Condition Regard Scale (MCRS), which measures the extent to which respondents find patients with a given medical condition to be enjoyable, treatable, and worthy of medical resources. 15 Clinicians expressing more negative attitudes about SCD patients were hypothesized to exhibit lower regard for these patients as measured by the MCRS.…”
Section: Methodsmentioning
confidence: 99%
“…Of particular interest is whether provider attitudes influence the provision of sickle cell care. Findings from a recent study by Ratanawongsa et al (2009) indicated that health care providers reported more positive attitudes toward Black patients who had counter-stereotypic traits (e.g., were well-educated and gainfully employed). It would be interesting to assess whether providers also report less positive attitudes toward Black patients with stereotypic traits (e.g., low educational attainment and unemployed).…”
Section: Implications For Clinical Outcomesmentioning
confidence: 96%
“…Using items from existing scales, the Assessment of Positive Regard, a novel 7-item scale, was developed. [24][25][26] This scale asks the provider to evaluate his or her own attitudes toward a patient in comparison to other patients; for example, ''Compared to other patients, I like this patient''. Responses are on a 5-point Likert scale (1 = strongly agree to 5 = strongly disgree).…”
Section: Main Measuresmentioning
confidence: 99%